2011
DOI: 10.1210/endo.152.1.9997
|View full text |Cite
|
Sign up to set email alerts
|

Materno-Fetal Cardiovascular Complications in Turner Syndrome after Oocyte Donation: Insufficient Prepregnancy Screening and Pregnancy Follow-Up Are Associated with Poor Outcome

Abstract: Context: Recombinant human GH treatment and oocyte donation (OD) have improved the quality of life in women with Turner syndrome (TS). However, life expectancy is reduced, mainly due to cardiovascular complications. Pregnancy may itself increase that risk and be associated with hazardous materno-fetal outcome. Objective: The objective of this study was to evaluate the materno-fetal outcome of ongoing pregnancies beyond 20 wk of gestation obtained by OD in TS. Design: This was a mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
82
7
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(97 citation statements)
references
References 37 publications
3
82
7
5
Order By: Relevance
“…In many studies, the outcomes of singleton and multiple pregnancies are not reported separately, which make their interpretation difficult. The perinatal mortality rate has been reported between 0 and 11% in published studies (225,226,231,232,233).…”
Section: Assisted Reproductive Technologies With Oocyte Donation (Od)mentioning
confidence: 99%
See 1 more Smart Citation
“…In many studies, the outcomes of singleton and multiple pregnancies are not reported separately, which make their interpretation difficult. The perinatal mortality rate has been reported between 0 and 11% in published studies (225,226,231,232,233).…”
Section: Assisted Reproductive Technologies With Oocyte Donation (Od)mentioning
confidence: 99%
“…In TS, the incidence of hypertensive disorders of pregnancy has been reported to be 35-67% in singleton pregnancies and as high as 100% in multiple pregnancies (222, 224, 225, 226, 231, 232, 233). The reported incidence of pre-eclampsia ranged between 18% and 44% in singleton pregnancies and 75-100% in multiples, while the cesarean section rate is as high as 82-100% (222, 224,225,226,231,232,233). In comparison, in oocyte recipients without TS, the rate of hypertensive disorders of pregnancy is 13-39%, and the cesarean section rate is 31-85% in singleton pregnancies (234).…”
Section: Assisted Reproductive Technologies With Oocyte Donation (Od)mentioning
confidence: 99%
“…Increasing numbers of women with TS are seeking pregnancy with modern reproductive technologies [57]. However, this population with a high prevalence of cardiac malformations is considered as very high-risk pregnancies [61][62][63][64]. The overall risk for major pregnancy complications in TS women is approximately 10% and the risk of maternal death is approximately 3.5% [64].…”
Section: Turner Syndrome and Pregnancymentioning
confidence: 99%
“…Recent guidelines recommend a cardiovascular check-up before pregnancy [59]. Aortic diameters above 25 mm/ m 2 , aortic coarctation, and a history of aortic surgery are considered contraindications to pregnancy [59,63,64].…”
Section: Turner Syndrome and Pregnancymentioning
confidence: 99%
See 1 more Smart Citation